Development of Assessment Methodology of Interaction between Customs Authorities and Participants of Foreign Economic Activity - Alexander SMEKALIN; Viktoria FROLOVA; Ekaterina SALIMONENKO; Alyona KARDAPOLTSEVA (Communications of International Proceedings, 2020)
Many problems cannot be solved without effective interaction between customs authorities and participants of foreign economic activity. In particular, this concerns the problems of accelerating customs operations when placing goods under customs procedures, the problems of simplifying customs operations, as well as exchanging information, optimizing and synchronizing the joint activities of customs authorities and participants of foreign economic activity. At the same time, as of today, there is no multi-purpose assessment methodology of interaction between customs authorities and participants of foreign economic activity, which would allow to assess the level of such interaction, as well as to identify the counteraction of the same interaction. The article considers the theoretical basis of interaction be-tween customs authorities and participants of foreign economic activity and reviews the theoretical and methodological aspects of the interaction between customs authorities and participants in foreign trade. The proposed assessment methodology of interaction between customs authorities and foreign trade participants is a set of indicators arranged in 4 groups: temporal indicators of interaction, indicators of the application of technology of electronic declaration, indicators of assessment of the level of risk of participants of foreign economic activity and overall indicators of interaction between customs authorities and participants of foreign economic activity. The methodology allows assessing the interaction and graphically representing the results obtained with the aim of identifying points of counteraction and the problem areas. To assess the effectiveness of interaction between a participant of foreign economic activity and customs authority, indicators can be considered separately or together. The approbation of the developed methodology on the example of the interaction between the participant of foreign economic activity and the customs authorities of Federal Customs Service of Russia at various levels has been carried out, practical recommendations have been given. The results of methodology approbation show its correctness, validity, and opportunity of practical application in the work of customs authorities and participants of foreign economic activity not only in the territory of the Russian Federation, but also in foreign countries with the possibility of its adaptation.
Keywords: Customs authority; participant of foreign economic activity; assessment of interaction effectiveness.